Fundamentals of Solid State Engineering - Razeghi, Manijeh (Springer, 2019)
Learning from Nature: Structure of Matter – Atoms Nature is the best innovator and teacher. Scientists know for a while now that all matter consists of atoms. The atom is the smallest part of any material element. So when we look around us and observe the material world, we know that these natural colors we see are the light emitted by atoms. But atoms consist of nuclei surrounded by clouds of electron and the light particles they emit are what we call the quanta of light or photons. At the end of the last century, we learned from the great physicist James Clerk Maxwell that light, and its individual quanta, the photons are electromagnetic waves emanating from atomic emission or more generally from oscillating charges. Electrons undergo a transition from a higher to a lower orbit in an atom that emits light and conversely can also absorb light. The detail of this transition determines the energy or wavelength of the light. This includes the entire spectrum of light from gamma rays to UV to visible and to the invisible infrared (IR) rays down to the THz. Our eyes can see only a small part of the total photonic spectrum, from 300 to 700 nm in wavelength. So it is understandable that one of the first and primary aims of physicists was to try making instrumentation in order to see the rest of the spectrum as well, using artificial eyes. These electronic eyes are made by materials engineering. Indeed this has been achieved now to a great extent, and the progress is so important that artificial eyes covering a much larger range of photonic energies are being made and are constantly being improved. This progress was acquired by first developing a deep understanding of the workings of atoms. In fact one can say that the last century was the century of exploring the atom and mastering the science of materials. The next century will be the century of genes and biological cells.